PENGEMBANGAN E-MODUL SEKUENSIAN PELAYANAN BERBASIS ARTICULATE STORYLINE 360 UNTUK SISWA TAHAP F SMK KULINER - Afifani, Arih Nur; Pangesthi, Lucia Tri; Handajani, Sri; Bahar, Asrul (Yayasan Amanah Nur Aman, 2025)
This study aims to determine the development results, material feasibility, media feasibility, and student responses to the Sequence of Service e-module based on Articulate Storyline 360. The method used is Research and Development (R&D) with the 4D model (define, design, develop, disseminate), but it was only carried out up to the develop stage due to time constraints. Validation was conducted by three material experts and three media experts, and a limited trial involved 31 eleventh-grade students of the Culinary Arts Program at SMKN 8 Surabaya. Data collection techniques used questionnaires and were analyzed using descriptive quantitative methods. The results showed that this e-module can be accessed both online and offline via a link or Android application. The evaluation from material experts obtained a percentage of 97.6%, categorized as very feasible, while the evaluation from media experts obtained a percentage of 96.7%, also categorized as very feasible. In addition, student responses to the e-module reached 84.3%, categorized as very good. Based on these results, the Sequence of Service e-module based on Articulate Storyline 360 is declared feasible to be used as a learning medium.